Routing Ambulances to Designated Centers Increases Access to Stroke Center Care and Enrollment in Prehospital Research. Issue 10 (October 2015) - Sanossian, Nerses; Liebeskind, David S.; Eckstein, Marc; Starkman, Sidney; Stratton, Samuel; Pratt, Franklin D.; Koenig, William; Hamilton, Scott; Kim-Tenser, May; Conwit, Robin; Saver, Jeffrey L.
<x xml:space="preserve">Abstract</x> Background and Purpose— Emergency medical services routing of patients with acute stroke to designated centers may increase the proportion of patients receiving care at facilities meeting national standards and augment recruitment for prehospital stroke research. Methods— We analyzed consecutive patients enrolled within 2 hours of symptom onset in a prehospital stroke trial, before and after regional Los Angeles County Emergency Medical Services implementation of preferentially routing patients with acute stroke to approved stroke centers (ASCs). From January 2005 to mid-November 2009, patients were transported to the nearest emergency department, whereas from mid-November 2009 to December 2012, patients were preferentially transported to first 9, and eventually 29, ASCs. Results— There were 863 subjects enrolled before and 764 after emergency medical service preferential routing, with implementation leading to an increase in the proportion cared for at an ASC from 10% to 91% (P<0.0001), with a slight decrease in paramedic on-scene to emergency department arrival time (34.5 [SD, 9.1] minutes versus 33.5 [SD, 10.3] minutes; P=0.045). The effects of routing were immediate and included an increase in proportion of receiving ASC care (from 17% to 88%; P<0.001) and a greater number of enrollments (18.6% increase) when comparing 12 months before and after regional stroke system implementation. Conclusions— The establishment of a regionalized emergency medical services system of acute stroke care dramatically increased the proportion of patients with acute stroke cared for at ASCs, from 1 in 10 to >9 in 10, with no clinically significant increase in prehospital care times and enhanced recruitment of patients into a prehospital treatment trial. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT00059332.